CdS-coated TiO2 nanotube layers: downscaling tube diameter towards efficient heterostructured photo-electrochemical conversion - Krbal, Miloš; Přikryl, Jan; Zazpe, Raul; Sopha, Hanna Ingrid; Macák, Jan (Royal Society of Chemistry, 2017)
Novel heterostructured solar cell based on TiO2 nanotube layers uniformly coated by CdS thin layer (using ALD) is presented. Downscaling the nanotube diameter (95 to 35nm) enhanced twice the UV and VIS light photocurrents. Further photocurrent improvement resulted from prior annealing of TiO2 nanotube layers from 300 to 600°C.